Exploration, Screening, and Application of Silica Solubilizing Bacteria and Silica Fertilizer to Suppress Fusarium Wilt Disease in Abaca - Werdiningtyas, Cyrilla Kinanti; Wibowo, Arif; Subandiyah, Siti; Widiastuti, Ani (Jurnal Fitopatologi Indonesia, 2023)
Exploration, Screening, and Application of Silica Solubilizing Bacteria and Silica Fertilizer to Suppress Fusarium Wilt Disease in Abaca Abaca (Musa textilis) is producing high quality natural fibre with the main problem is fusarium wilt disease caused by Fusarium oxysporum f. sp. cubense TR4. The study aims to obtain silica solubilizing bacteria (SSB), determine the role of SSB and silica fertilizer to inhibit fusarium and to stimulate plant growth. Six isolates of SSB were obtained from healthy abaca rhizosphere, three of them had antagonistic activity against F. oxysporum f. sp. cubense TR4. The four treatments tested showed no different severity of fusarium wilt. Likewise, the four treatments did not show any difference in the observed growth variables. Silica solubilizing bacteria and silica fertilizer have not been able to control F. oxysporum f. sp. cubense TR4. Therefore, abaca proved to be susceptible to F. oxysporum f. sp. cubense TR4.